203k views
5 votes
F(x) =X+4
g(x) = 3x² -7
Find (f-g) (x)

Algebra 2 sem 1

F(x) =X+4 g(x) = 3x² -7 Find (f-g) (x) Algebra 2 sem 1-example-1
User Llovett
by
4.4k points

1 Answer

7 votes

Answer:


B. ~(f+g)(x)=6x^3+4x-2

Explanation:


f(x)=2x^2+4x-5


g(x)=6x^3-2x^2+3


Find~(f+g)(x)


=2x^2+4x-5+6x^3


-2x^2+3


(f+g)(x)=6x^3+4x-2

--------------------------------

hope it helps....

have a great day!!

User Rmannn
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.